(3GdMdd GdehTjI aj PcQ GdCNHGQ GdeQGcTjIs
(3ChdgG (B:s
(3GdMeO ddg GdPi NQL GdCehQ Ydi eTjFJI JbOjQg s
(3BNQgG (B:s
(3hgPG eG MVQ hGdSdGe hUdi Gddg Ydi SjOfG hehdGfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B192 (3C (B- (3UH (B259s
(3WHY efShHkG Edi dSGf GdOjf Hf GdNWjHs
(3Cdag GdeDda GdeLghd HGdCfOdS aj YgO GdSdWf GdZfj HGddg eMeO GdNGeS GdfUQj haQZ ef JCdjag (B783 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs